Kepuasan Kerja Dipengaruhi Oleh Kompensasi, Stres Kerja Dan Disiplin Kerja Pegawai Kantor Sekretariat Dewan Perwakilan Rakyat Daerah Penajam Paser Utara - Azroo Aqiilah Achmad Jais Mandrow, Lutfiah; Ariani, Misna; Arrywibowo, Imam (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
This study aims to analyze the effect of compensation, work stress, and work discipline on employee job satisfaction at the Secretariat Office of the Regional People's Representative Council (DPRD) of Penajam Paser Utara Regency. Compensation, work stress, and work discipline are crucial factors influencing employee job satisfaction. The research employs a quantitative method supported by Smart PLS software and a purposive sampling technique, involving 35 respondents who are employees of the DPRD Secretariat of Penajam Paser Utara. Data were collected using questionnaires measuring variables of compensation, work stress, work discipline, and job satisfaction. The results show that compensation has a positive and significant effect on employee job satisfaction, while work stress does not significantly affect job satisfaction. Likewise, work discipline does not significantly influence job satisfaction. The conclusion of this study is that improving employee job satisfaction can be achieved through fair and adequate compensation, effective management of work stress, and consistent enforcement of work discipline. These findings are expected to provide input for the DPRD Secretariat of Penajam Paser Utara in designing human resource policies to enhance employee welfare and productivity.